2020
DOI: 10.12890/2020_001409
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation Induced Consciousness - A Case Report in an Elderly Patient

Abstract: Cardiopulmonary resuscitation-induced consciousness is a rarely described and often misunderstood phenomenon, although it can be encountered. High quality cardiopulmonary resuscitation (CPR) may lead a patient to recover consciousness while in cardiac arrest. The authors present the case of an 89-year-old male patient who received CPR after a cardiac arrest. Spontaneous movements during CPR were noted and prompted several CPR interruptions. These movements immediately stopped during chest compression pauses. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Twenty-four case reports or series that described 31 cases of consciousness during CPR were published since 1962, with sedative drugs being used in ≈30%. 157–180 Existing drug regimens were identified that included the use of ketamine, midazolam, or fentanyl or a combination of these drugs.…”
Section: Advanced Life Supportmentioning
confidence: 99%
“…Twenty-four case reports or series that described 31 cases of consciousness during CPR were published since 1962, with sedative drugs being used in ≈30%. 157–180 Existing drug regimens were identified that included the use of ketamine, midazolam, or fentanyl or a combination of these drugs.…”
Section: Advanced Life Supportmentioning
confidence: 99%
“…Our resuscitation team faced challenges differentiating between CPRIC and ROSC, leading to confusion and perhaps inappropriate interventions. The patient’s motor movements during CPR posed a specific treatment dilemma, as balancing them with uninterrupted CPR and avoiding complications and obstacles in achieving ROSC was essential [ 1 , 2 ]. The causes of CPRIC are still unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of controlled trials and evidence-based protocols for managing CPRIC contributes to the treatment dilemma faced by healthcare providers. Further study is required to determine whether these people should be physically restrained or sedated [ 2 ]. Further research, a review of reported cases, sedation and medication guidelines, and novel interventions are necessary to guide healthcare providers in making informed treatment decisions and improving outcomes for patients experiencing CPRIC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations